2017
DOI: 10.1589/jpts.29.1305
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic field with or without exercise therapy in the treatment of benign prostatic hyperplasia

Abstract: [Purpose] To investigate the effect of pulsed electromagnetic field with or without exercise therapy in the treatment of benign prostatic hyperplasia. [Subjects and Methods] Sixty male patients aged 55–65 years with benign prostatic hyperplasia were invited to participate in this study. Patients were randomly assigned to Group A (n=20; patients who received pulsed electromagnetic field in addition to pelvic floor and aerobic exercises), Group B (n=20; patients who received pulsed electromagnetic field), and Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Instead, there was no statistically significant reduction in total PSA and IPSS. These results are partially consistent with the results of previous studies such as that one of Elgohary et al (13) which demonstrated the effectiveness of pulsed electromagnetic fields alone or in association to exercise therapy in the treatment of benign prostatic hypertrophy in terms of IPSS improvement and reduction of bladder residue after voiding and that of Tenuta et al (14) which likewise demonstrated the effectiveness of pulsed electromagnetic fields in terms of prostate volume reduction and IPSS enhancement. In neither of the two studies however the pulsed electromagnetic fields were compared with the standard drug therapy for benign prostatic hypertrophy.…”
Section: Discussionsupporting
confidence: 91%
“…Instead, there was no statistically significant reduction in total PSA and IPSS. These results are partially consistent with the results of previous studies such as that one of Elgohary et al (13) which demonstrated the effectiveness of pulsed electromagnetic fields alone or in association to exercise therapy in the treatment of benign prostatic hypertrophy in terms of IPSS improvement and reduction of bladder residue after voiding and that of Tenuta et al (14) which likewise demonstrated the effectiveness of pulsed electromagnetic fields in terms of prostate volume reduction and IPSS enhancement. In neither of the two studies however the pulsed electromagnetic fields were compared with the standard drug therapy for benign prostatic hypertrophy.…”
Section: Discussionsupporting
confidence: 91%
“…37 To the best of our knowledge, only two human studies have used PEMF in the treatment of BPH. 23,24 So far, different devices have been used for PEMFs therapy, tailoring treatment duration according to tissue-specific conductivity and field strengths produced by the device used. In this context, our device was selected taking into account its specific technical features.…”
Section: Kidney Functionmentioning
confidence: 99%
“…The device used was small, portable, and easy to apply at home by the patient himself. In the previously mentioned studies, 23,24 both of the devices required hospital admission and administration by healthcare professionals with longer daily treatment duration (30 minutes in-office application 5 days/week).…”
Section: Kidney Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many physiotherapy modalities used in wound healing as laser and exercises [9, 10]. Pulsed radio frequency electromagnetic energy (PRFE) electrotherapy has recently been given a new focus, with a range of case reports showing positive results in improving hyperplasia and chronic wound healing [11,12].…”
Section: Introductionmentioning
confidence: 99%